2015
DOI: 10.5152/akd.2014.5747
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between extent and complexity of coronary artery disease and different left ventricular geometric patterns in patients with coronary artery disease and hypertension

Abstract: Objective:The relationship between severity of coronary artery disease (CAD) and left ventricler (LV) hypertrophy in hypertensive patients is well known. However, the association between the extent and complexity of CAD assessed with SYNTAX score (SS) and different LV geometric patterns has not been investigated. We aimed to investigate the association between SYNTAX score and different LV geometric patterns in hypertensive patients.Methods:The study had been made in our clinic between January 2013 and August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…COPD, HF, DM and higher SYNTAX score were found to be independent variables predicting the development of POAF. In previous studies, advanced age, male gender, chronic HF, preoperative AF attacks, COPD, chronic renal disease, DM and rheumatic heart disease, metabolic syndrome, and obesity were reported to be preoperative clinical parameters predicting the development of POAF 10)11)…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…COPD, HF, DM and higher SYNTAX score were found to be independent variables predicting the development of POAF. In previous studies, advanced age, male gender, chronic HF, preoperative AF attacks, COPD, chronic renal disease, DM and rheumatic heart disease, metabolic syndrome, and obesity were reported to be preoperative clinical parameters predicting the development of POAF 10)11)…”
Section: Discussionmentioning
confidence: 98%
“…Kralev et al5) reported that the incidence of CAD was 34% in patients with AF. Several studies have demonstrated a relationship between CAD and POAF 10)11). The SYNTAX score takes into account anatomic complexities including calcification, total occlusion, bifurcation lesions, thrombus, and long lesions.…”
Section: Discussionmentioning
confidence: 99%
“…CIMT and EFT are non-invasively and reliably measured parameters that are shown to be closely related to coronary atherosclerosis. 24 , 25 These parameters can be measured with negligible operator dependence, and their reproducibility is excellent. 26 , 27 , 28 That is the reason why we hypothesized that CIMT and EFT are good candidates for further improvement of SSII.…”
Section: Discussionmentioning
confidence: 99%
“…It is used in the estimation of long-term outcomes of CAD and in the selection of the treatment modality. Its efficacy has been demonstrated in various studies [7][8][9].…”
Section: Introducti̇onmentioning
confidence: 99%